EVALUASI USABILITY WEBSITE BUKALAPAK DAN TOKOPEDIA MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ) - Putra, I Gusti Putu Agung Arka; Juliantara. KW, Pande Putu Ode; Gunawan, I Made Agus Oka; Indrawan, Gede (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
This research aims to compare elements of usability and user experience on the e-commerce platforms Bukalapak and Tokopedia. Usability quality has important significance because if an application or website has optimal usability, users will be able to use it easily. Users who feel disappointed or have difficulty interacting with a website are likely to leave the platform and look for an alternative that is easier to use. Therefore, usability evaluation becomes crucial for e-commerce websites. Measurements were carried out using the User Experience Questionnaire (UEQ) method which involves several aspects, including attractiveness, perception, efficiency, dependability, stimulation and novelty. The results of evaluating user usage and experience on these two e-commerce websites, using the UEQ method, show that Bukalapak achieved an Attractiveness value of 0.80, Perspicuity of 0.83, Efficiency of 0.63, Dependability of 0.53, Stimulation of 0.74, and Novelty of 0.38. Meanwhile, Tokopedia achieved an Attractiveness score of 1.24, Perspicuity of 1.08, Efficiency of 1.20, Dependability of 1.19, Stimulation of 0.96, and Novelty of 0.70. Therefore, it can be concluded that Tokopedia shows better performance than Bukalapak in terms of usability and user experience on the e-commerce platform.